2017
DOI: 10.1016/j.ajpath.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mouse Model of Staphylococcus aureus Vascular Graft Infection

Abstract: Staphylococcus aureus causes very serious infections of vascular grafts. Knowledge of the molecular mechanisms of this disease is largely lacking because of the absence of representable models. Therefore, the aim of this study was to set up a mouse model of vascular graft infections that closely mimics the human situation. A catheter was inserted into the right carotid artery of mice, which acted as a vascular graft. Mice were infected i.v. using 8 different S. aureus strains, and development of the infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Specifically, the interstitial porosity, surface tension, and electronegativity of synthetic vascular graft materials have previously been shown to attract and support bacterial adherence. 27,28 The ability of bacteria within contaminated ePTFE to persist without adequate clearance by host immune cells, resist antibiotic therapy, and produce sustained infections and biofilms 14,25,29 may be connected to k i r k t o n e t a l h u m a n a c e l l u l a r v e s s e l s r e s i s t i n f e c t i o n i n a p r e c l i n i c a l m o d e l interstitial colonization and subsequent inaccessibility of bacteria within the ePTFE matrix. Interstitial bacterial accumulation within the ePTFE matrix has previously been shown in vitro 30 as well as in vivo here in our study and by others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the interstitial porosity, surface tension, and electronegativity of synthetic vascular graft materials have previously been shown to attract and support bacterial adherence. 27,28 The ability of bacteria within contaminated ePTFE to persist without adequate clearance by host immune cells, resist antibiotic therapy, and produce sustained infections and biofilms 14,25,29 may be connected to k i r k t o n e t a l h u m a n a c e l l u l a r v e s s e l s r e s i s t i n f e c t i o n i n a p r e c l i n i c a l m o d e l interstitial colonization and subsequent inaccessibility of bacteria within the ePTFE matrix. Interstitial bacterial accumulation within the ePTFE matrix has previously been shown in vitro 30 as well as in vivo here in our study and by others.…”
Section: Discussionmentioning
confidence: 99%
“…13 It has been shown that biofilms produced by S. aureus readily form on contaminated ePTFE vascular grafts and survive for weeks despite active host immune responses and high blood flow shear stresses. 14 We have developed an investigational tissue-engineered acellular blood vessel using primary human vascular cells that are seeded on a rapidly degrading polymer scaffold and cultured to form a tissue, which is then decellularized to remove the cells. The resulting engineered human acellular vessel (HAV) is a robust tube of human extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Gram staining or immunohistochemical methods, FISH combines molecular detection of microorganisms with fluorescence microscopy and has been increasingly used for analysis of biofilm‐associated infections . FISH can be applied to in vitro samples as well as to ex vivo samples from animal models or patients . Since FISH‐probes hybridize ribosomal RNA, the signal intensity correlates to the ribosome content and consequently activity of the cells.…”
Section: Bacteriological Aspects Of Odri Studiesmentioning
confidence: 99%
“…). Consequently, FISH is increasingly used in infection models, although it is labor intensive and rather restricted to specialized laboratories.…”
Section: Bacteriological Aspects Of Odri Studiesmentioning
confidence: 99%
“…The phenomenon of biofilm formation, where adherent bacteria on vascular prostheses or felt is not uncommon and was found to be a factor in the pathogenesis of late graft infection (38,39) . This has been further explored and confirmed as some pathogens, specifically Staphylococcus aureus, have an increased tendency for biofilm development (40) . If synthetic prostheses are more prone to develop infection due to this is still controversial.…”
Section: The Aortic Valve and Rootmentioning
confidence: 91%